Relationship between the distance and time of the glide to touch the wall in a unilateral arm amputee swimmer - Tanigawa, T.; Kumamato, K.; Kataoka, H.; Awatani, T.; Tachi, M. (XIII th International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2018)
This case study aimed to clarify the relationship between the distance and time of the glide to touch the wall at the finish in a unilateral arm amputee swimmer. The participant was a female unilateral arm-amputee Japanese national team swimmer (Impairment Classification S9) who had participated in the Rio 2016 Paralympics. In the trial, the participant swam front-crawl with maximum effort without taking a breath for 10 m, until she reached the wall. The swimmer was instructed to extend her non-impaired arm and reach for the wall after she recognized the marker set on the floor of the pool (depth, 1.2 m). The position of the marker was randomly set at 1.5, 2, 2.5, 3 and 3.5 m from the wall in the trials. The participant swam 20 times (four times for each marker position) with sufficient rest between the trials. Each trial was recorded with surface and underwater cameras. The video images were captured into a personal computer and analyzed using a motion analysis software. We measured the time from the last hand entry of the non-impaired side to when the swimmer touched the wall and defined it as finishing-time. Also, the estimated finishing-time was calculated as the distance between the swimmer`s head at the last hand entry and the wall (finishing-distance) divided by the free-swimming velocity. Then the difference between measured and estimated finishing-time was calculated as time-loss, which meant the loss of time during the glide to reach for the wall. In the trials, the finishing-distance and the time-loss were 0.77 to 3.30 m and -0.23 to 0.49 seconds, respectively. There was a significant positive correlation between the time-loss and the finishing-distance (y = 0.2801x - 0.4494, r = 0.867, p = 0.000). These results indicated that the swimmer must approach the wall in a way that shortens the distance of glide to perform the touch at finishing phase.